2020
DOI: 10.3390/su13010131
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Organic Food Consumers—Serbia Case-Study

Abstract: In this paper, the authors analyze products from the organic farming system from consumption and consumers. The research aimed to determine the characteristics of the Serbian organic market, discover attitudes, practices, and features of different organic food consumers and identify factors that influence organic products’ purchase. This was done following the theoretical framework of green marketing, which refers to the holistic management process responsible for identifying, anticipating, and satisfying cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
(62 reference statements)
0
14
1
2
Order By: Relevance
“…This result is supported by previous study on organic food in Vietnam conducted by Van and Hui (2019) [28] which mentioned that the percentage of type of people who value highly food quality named as conservative people was also the highest compared to the other clusters (trendsetter and unengaged to organic food). Differing from Radojevic' et al's [53] study in Serbia regarding organic food purchase, the consumer cluster which concern in organic food was not the highest in comparison to the others. The consumers mostly buy foods based on its aesthetic value, the ease of recognition of the product label and information, and the healthiness that has not to be organic food.…”
Section: Discussioncontrasting
confidence: 57%
“…This result is supported by previous study on organic food in Vietnam conducted by Van and Hui (2019) [28] which mentioned that the percentage of type of people who value highly food quality named as conservative people was also the highest compared to the other clusters (trendsetter and unengaged to organic food). Differing from Radojevic' et al's [53] study in Serbia regarding organic food purchase, the consumer cluster which concern in organic food was not the highest in comparison to the others. The consumers mostly buy foods based on its aesthetic value, the ease of recognition of the product label and information, and the healthiness that has not to be organic food.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, the Slovak market is signalling the same shift, according to Kádeková et al [26], whose research paper suggested that the key factor for organic food purchase is its quality and the information that the food is pesticide-free; the price was found to be the next most important thing. In addition, Hidalgo-Baz, Martos-Partal and González-Benito [27] consider the product quality to be the key factor on the Spanish market, while, in Serbia [28], a choice oriented toward organic food is determined by its price and quality (also related to the socio-economic characteristics of consumers), concluding that the producers' marketing should predominantly target consumers who are already "more environmentally and health-conscious".…”
Section: Introductionmentioning
confidence: 99%
“…Also, the growth of domestic demand for these products would significantly accelerate the development of organic production. According to Radojević et al [ 47 ], to boost demand, it is necessary to improve consumer knowledge about what organic production is and how products from this production system are appropriately labelled. This is crucial due to a positive impact of organic production on the environment and the sustainability of the food system [ 48 ].…”
Section: Resultsmentioning
confidence: 99%